PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA TOKO FUN’S BOUQET BALLOON - Maryani Farwati; Tata Sutabri (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Toko Fun's Bouqet Balloon is a store that sells various flower-shaped balloon bouquets. The sales system utilized by Toko Fun's Bouqet Balloon only employs social media platforms such as Instagram for its online sales. However, this method is still deemed suboptimal due to the low sales and inadequate organization of sales data. Therefore, based on the problems encountered by Toko Fun's Bouqet Balloon, the author designed an online sales information system using a website with internet access that will display information about the products for sale. This research uses the waterfall methodology, which simplifies the process of designing and creating a sales website. The resulting website was designed with a simple layout for easy accessibility. However, the speed of loading web pages and the addition of features still need improvement to attract potential buyers or customers